Testicular Cancer Mortality in Chile: Is it as high as we think? 41 years of experience in a single center - Nicolás Pieressa P; José Rojas C; Carolina Bonomo M; José Villena H; Ítalo Raineri V; Sebastián Oporto U; Cristián Alliende; Miguél Sarrás J; Christopher Horn B; Bruno Vivaldi J; Iván Saez V; Felipe Mandujano T; et al. (Archive of Urological Research - Peertechz Publications, 2019)
Introduction: Testicular cancer carries a good prognosis, with survival rates over 70% at any stage. According to the GLOBOCAN database, Chile has the highest mortality rate worldwide, without a clear explanation of why this is the case. The objective of this study is to contrast the observed deaths in a chilean center during a 41-year period, to the national data previously reported by GLOBOCAN. Methods: For this retrospective descriptive study, data was retrieved from medical records from every patient diagnosed with testicular cancer between the years 1978-2019 in our center, and their death certificates were assessed for comparison. Histological type, staging, adjuvant treatment, and cause of death, among other variables, were analyzed.  Results: Out of 255 patients diagnosed with testicular cancer, 239(93.7%) were alive at the time of data collection. Out of the 16 recorded deaths, 5(2%) had testicular cancer as cause of death, two out of these five patients had early stage cancers, completed 5 years follow-up without relapse, had multiple comorbidities, and had unspecific information in the death certificate. Thus, testicular cancer cannot be attributed with certainty as the cause of death in those patients. Conclusion: Chile has the highest mortality rate for testicular cancer worldwide. In our center 40% of the patients that have testicular cancer as cause of death had presumably been incorrectly registered in the death certificate. A possible explanation for the high mortality in Chile could be an incorrect registration of testicular cancer as cause of death.